1993
DOI: 10.1159/000109474
|View full text |Cite
|
Sign up to set email alerts
|

Release of Dopamine from Carotid Sinus Nerve Fibers Innervating Type I Cells in the Cat Carotid Body

Abstract: This study presents evidence that dopaminergic neurons innervate the cat carotid body. Immunocytochemical studies revealed many tyrosine hydroxylase (TH)-positive nerve fibers in the carotid body which establish extensive contacts with type I cells. All TH-positive intralobular profiles disappeared with chronic carotid sinus nerve (CSN) section, but survived sympathectomy following removal of the superior cervical ganglion. The level of endogenous dopamine (DA) in the CSN was higher than that for norepinephrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The first group have nerve endings rich in TH and can synthesise catecholamines, of which dopamine is the major final form, with those fewer endings containing noradrenaline attributable to a sympathetic nerve origin (33, 277). These catecholaminergic fibers make extensive synaptic, often calyciform, contact with type I cells.…”
Section: Innervation and Communications Of The Carotid Bodymentioning
confidence: 99%
“…The first group have nerve endings rich in TH and can synthesise catecholamines, of which dopamine is the major final form, with those fewer endings containing noradrenaline attributable to a sympathetic nerve origin (33, 277). These catecholaminergic fibers make extensive synaptic, often calyciform, contact with type I cells.…”
Section: Innervation and Communications Of The Carotid Bodymentioning
confidence: 99%
“…Further, the magnitude of the CSN excitatory response appears to be blunted by the concurrent action of inhibitory neurotransmitters such as GABA and dopamine (Alcayaga et al, 1999 ; Iturriaga et al, 2009 ; Nurse, 2010 ). In the case of dopamine, it is possible that its release from activated afferent C fibers during chemoexcitation may lead to autocrine-paracrine stimulation of inhibitory D2 receptors (D2R) on nearby type I cells and/or afferent nerve terminals (Benot and Lopez-Barneo, 1990 ; Almaraz et al, 1993 ; Iturriaga et al, 2003 ).…”
Section: Synaptic Transmission Between Chemoreceptor Type I Cells Andmentioning
confidence: 99%
“…These data suggest that stimulation of D2R on chemosensory petrosal neurons and their terminals causes a decrease in intracellular cAMP leading to inhibition of the cAMP-gated I h channels containing HCN4 subunits (Zhang et al, 2017 ). In this scenario, the source of dopamine is predominantly from nearby type I cells though it may include terminals of excited catecholaminergic C fibers of petrosal CB chemoafferents (Almaraz et al, 1993 ; Iturriaga et al, 2003 ).…”
Section: Synaptic Transmission Between Chemoreceptor Type I Cells Andmentioning
confidence: 99%
“…As outlined above, D 2 -dopamine receptors on glomus cells likely have an autoreceptor function, but these receptors are also postsynaptic to chemoafferents that form reciprocal synapses with glomus cells (Alamaraz et al, 1993;Kummer and Habeck 1992). Retrograde tracing studies have demonstrated that a substantial number of retrogradely labeled neurons in the petrosal ganglion contain TH immunoreactivity (Alamaraz et al, 1993; or TH mRNA (Czyzyk- Krzeska et al, 1991).…”
Section: Catecholaminergic Neurotransmitter Systems Involvedmentioning
confidence: 99%
“…Retrograde tracing studies have demonstrated that a substantial number of retrogradely labeled neurons in the petrosal ganglion contain TH immunoreactivity (Alamaraz et al, 1993; or TH mRNA (Czyzyk- Krzeska et al, 1991). Furthermore, detailed experiments performed by Alamaraz et al (1993), have shown that endogenous dopamine can be measured and dopamine can be synthesized in the carotid sinus nerve of the adult cat. Thus, in adult models release of dopamine from chemoafferent neurons in response to hypoxia may also influence the chemotransduction process in the carotid body.…”
Section: Catecholaminergic Neurotransmitter Systems Involvedmentioning
confidence: 99%